Speech Delay Intervention through Milieu Teaching Approach in Reading and Singing Activities: A Single-Case Study - Roisatul Hidayah; Raden Roro Anisa Anggi Dinda; Melisa Melisa; Elga Andriana (International Conference on Psychology and Education (ICPE), 2023)
This study aims to provide interventions to parents about understanding milieu teaching methods in reading and singing activities, as well as encouraging the child to produce new vocabulary. Participants in this study were one boy aged 2 years and 5 months who was diagnosed with speech delay and his parent. This research design is a case study with psychoeducational for subjects. The intervention design was carried out in three stages, baseline, psychoeducational, and maintain. As a result, this study has succeeded in providing parents with an understanding of milieu teaching approach technique in reading and singing activities. This implies that the approach is appropriately applied for the parents in this study. On the other hand, by the end of the intervention session, the subject had not been able to produce words. Several factors such as physical condition, environment, and time management, influence the intervention in this case. Intervention results will reach the maximum and comprehensive point if carried out consistently and continuously.